Membangun Keunggulan Kompetitif: Penerapan OEE dan Six Big Losses untuk Meningkatkan Efisiensi Mesin I-12 di PT. BI - Savitri, Alya; Neneng Winarsih (Fakultas Teknik Universitas Tulang Bawang, 2024)
BI is a company that operates in the plastic packaging manufacturing industry. The main problem faced by PT. BI lies in the productivity and efficiency of the I-12 machine. The operational disruptions that occurred were a large number of breakdowns and less than optimal production levels so this machine did not reach the desired maximum capacity. The impact of these conditions can be detrimental to the company with the potential to reduce machine productivity and efficiency, as well as the possibility of incurring high costs. This research aims to evaluate the effectiveness of the I-12 engine by applying the Overall Equipment Effectiveness (OEE) method. According to the calculated data, the average Overall Equipment Effectiveness value from January to June 2022 is 81.32%, which means it does not meet the standards set by the Japan Institute of Plant Maintenance. Reduce speed losses on the I-12 engine have the largest percentage of the six big loss factors, namely 68.37%, which is the main cause of the decline in the effectiveness of the engine. Therefore, an in-depth analysis using a fishbone diagram is needed to find out the root cause of the problem. Keywords: Efficiency, Effectiveness, Overall Equipment Effectiveness, Six Big Losses